Evaluation of Critical Parameters to Improve Slope Drainage System. (21st December 2017) - Weng Long, Yong; Taib, Siti Noor Linda; Selaman, Onni Suhaiza
Abstract : This study focuses on identifying and evaluating critical parameters of various drainage configurations, arrangement, and filter which affect the efficiency of water draining system in slopes. There are a total of seven experiments with different types of homogeneous soil, drainage envelope, filter material, and quantity of pipes performed utilizing a model box with a dimension of 0.8 m × 0.8 m × 0.6 m. The pipes were orientated at 5 degrees from the horizontal. Rainfall event was introduced via a rainfall simulator with rainfall intensity of 434.1 mm/h. From the experiments performed, the expected outcomes when utilizing double pipes and geotextile as envelope filter were verified in this study. The results obtained from these experiments were reviewed and compared with Chapter 14 "Subsurface Drainage Systems" of DID's Irrigation and Agricultural Drainage Manual of Malaysia and the European standard. It is recommended that the pipe installed in the slope could be wrapped with geotextile and in tandem with application of granular filter to minimize clogging without affecting the water discharge rate. Terzaghi's filter criteria could be followed closely when deciding on new materials to act as aggregate filter. A caging system could be introduced as it could maintain the integrity of the drainage system and could ease installation.